PECULIARITIES OF ECONOMIC AND LEGAL REGULATION OF MICROFINANCE IN ARMENIA - Artak T. Yarazyan (Статистика и экономика, 2016)
This article reveals the key features ofthe regulation of microﬁnance institutions (MFIs) and microﬁnance services in the Republic of Armenia, through carefulanalysis of the legal framework. The article discusses the process of becomingmicrocredit regulatory laws and regulations, their current status and differences from the Russian experience. Particularattention is given to the Central Bank ofArmenia (CBA), as the sole regulator ofmicrofinance, which is responsible forlicensing, sets prudential standards andrequirements and regulates the executionof the latter.